Sphingolipidomic study of davidiin-treated HepG2 human hepatocellular carcinoma cells using UHPLC-MS. Issue 87 (5th December 2017) - Xie, Li-Min; Yau, Lee-Fong; Jiang, Zhi-Hong; Zhang, Li-Yan; Xia, Yun; Wang, Jing-Rong
Abstract : An improved sphingolipidomic approach demonstrated elevated dihydroceramide and sphinganine, which may be due to the inhibition effect of davidiin on DES. Abstract : Davidiin, a natural product originating from Polygonum capitatum, has been proven to possess anti-hepatocellular carcinoma activity. To explore the mechanisms underlying the activity of davidiin, sphingolipids (SPLs) in HepG2 human hepatocellular carcinoma cells with or without the treatment of davidiin were comprehensively analyzed using an improved sphingolipidomic approach established in our lab. A total of 133 SPLs were identified and quantified by using the multiple reaction monitoring (MRM) technique. The results revealed an extensive elevation of dihydroceramide (DHCer) and sphinganine (Sa) induced by davidiin in HepG2 cells, which potentially mediate the cytotoxicity of davidiin. Based on the alteration of upstream and downstream products in the biosynthesis and metabolism network of SPLs, the elevated DHCer and Sa are proposed to result from the inhibition effect of davidiin on dihydroceramide desaturase (DES), which was further confirmed by in vitro assay. Given the emerging role of DES as a therapeutic target of cancer, our results not only provided evidence for the mechanisms underlying the cytotoxicity of davidiin, but also underscored the potential of ellagitannin as a new group of aromatic natural products acting on DES.